2018
DOI: 10.1111/bjhp.12340
|View full text |Cite
|
Sign up to set email alerts
|

Do interventions containing risk messages increase risk appraisal and the subsequent vaccination intentions and uptake? – A systematic review and meta‐analysis

Abstract: Overall, there is a lack of good-quality primary studies, and existing interventions are suboptimal. The inclusion of additional BCTs, including those to target efficacy appraisals, could increase intervention effectiveness. The protocol (CRD42015029365) is available from http://www.crd.york.ac.uk/PROSPERO/. Statement of contribution What is already known on this subject? Previous research indicates that an increase in risk appraisal is associated with increased uptake in health-related behaviours. Research su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
(38 reference statements)
0
20
0
Order By: Relevance
“…This research provides novel targets, such as maladaptive response rewards that can and should be examined when seeking to modify individuals' evaluations of the risks associated with seasonal influenza vaccination. Further, although relatively few studies have sought to increase efficacy appraisals (Parsons et al, 2018), this research provides further evidence of the importance of self-efficacy and response efficacy in predicting intention to vaccinate. However, while this study examined the relative predictive strength of PMT constructs in predicting intention through examination of beta weights and structure coefficients, as a crosssectional study it necessarily cannot provide insight into which of these constructs would provide the most appropriate intervention targets.…”
Section: Limitationsmentioning
confidence: 70%
See 1 more Smart Citation
“…This research provides novel targets, such as maladaptive response rewards that can and should be examined when seeking to modify individuals' evaluations of the risks associated with seasonal influenza vaccination. Further, although relatively few studies have sought to increase efficacy appraisals (Parsons et al, 2018), this research provides further evidence of the importance of self-efficacy and response efficacy in predicting intention to vaccinate. However, while this study examined the relative predictive strength of PMT constructs in predicting intention through examination of beta weights and structure coefficients, as a crosssectional study it necessarily cannot provide insight into which of these constructs would provide the most appropriate intervention targets.…”
Section: Limitationsmentioning
confidence: 70%
“…There is evidence that interventions that increase risk appraisal and coping appraisal can be effective at increasing vaccination uptake (Sheeran, Harris, & Epton, 2014). However, interventions have often been ineffective at bringing about changes risk appraisal (Parsons, Newby, & French, 2018). This research provides novel targets, such as maladaptive response rewards that can and should be examined when seeking to modify individuals' evaluations of the risks associated with seasonal influenza vaccination.…”
Section: Limitationsmentioning
confidence: 99%
“…Many traditional information and educational tools—such as fact sheets or posters—have been shown to lack effectiveness and have no or little impact on vaccine hesitancy, or even entail a risk to increase hesitancy [29, 36]. Communicating about the risk of diseases may have the power to enhance people’s perceptions of risk, but does not necessarily have the intended effect on intentions to vaccinate [9, 37]. Worse than that, trying to correct misperceptions about vaccination can have the opposite effect, i.e.…”
Section: Ways To Increase Acceptance and Demandmentioning
confidence: 99%
“…Vaccine promotional programmes may, unwittingly, reinforce this negative message by just framing the benefit of vaccination in terms of avoidance of risk. A meta-analysis of interventions to improve vaccination uptake showed that the commonest approach was “ Information about Health Consequences ” where discussion of risk was a major theme [ 105 ]. Where a positive message is delivered, it often emphasizes the social benefit of vaccination (via herd or community protection).…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases at least, individuals may be more strongly motivated to vaccinate by the prospect of individual rather than societal benefit [ 108 ], and there is strong evidence that simply providing information about risks to health or the risk of failing to carry out the suggested health behaviour (i.e. vaccination) may not be sufficient to promote behavioural change [ 96 , 105 ]. Message framing is thus crucial: while risk – both of disease and of potential vaccine-related adverse events – needs to be addressed, it may be more productive to focus more on benefits (both to the individual and to society at large) and social norms.…”
Section: Introductionmentioning
confidence: 99%